Guidebook to Carbon Neutrality in China Macro and Industry Trends under New Constraints. - CICC Research; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This Open Access publication focuses on China$1 (Bs goal of achieving peak carbon emissions in 2030 and carbon neutrality by 2060. The book is the first to systematically build a framework combining a top-down and bottom-up analysis of this acute topic. What does carbon neutrality mean for economics in China? Might it imply stagflation or is it an opportunity to maximize the potential of green manufacturing? The book offers a comprehensive analysis of how the pursuit of carbon neutrality may influence the development of China's economy, and the country's biggest industries, while foreseeing the likely changes in people's lifestyles. In total, the book constructs a comprehensive path for China's carbon neutrality drive from the perspective of the green premium. This effort lays the foundation for a discussion of the country's emissions reduction plan. The book goes further, calculating the investment required for different sectors to achieve carbon neutrality, and illustrating the roles of carbon pricing and green finance in this undertaking. The book$1 (Bs information comes from a network of primary sources, including experts in the field and noted academics, to depict potential low-carbon roadmaps and green transitions in major industries. Emphasized is green development in sectors that will be critical to civilization, including in technology, energy, manufacturing, transportation, and urban planning, which are backed by in-depth discussions and analyses. Accessible and academically rigorous, the work is anchored in the economics of carbon neutrality, extends to potential policy implications and identifies investment opportunities. This valuable reference will attract readers interested in public policy, economics, finance, and investors who seek to better understand China's prospects in the low-carbon economy of the near future.s
Chapter 1. Exploring road to carbon neutrality: Crossroads between the past and next 40 years -- Chapter 2. Carbon neutrality: Innovation and fairness -- Chapter 3. Is there a unified carbon price for all industries? -- Chapter 4. Green finance: Clarifying functions and capacity -- Chapter 5. Green technology: From quantity to quality -- Chapter 6. Green energy: A new chapter in China -- Chapter 7. Green manufacturing: Carbon emission reduction roadmap from perspective of green premium -- Chapter 8. Green transportation: A challenging road to carbon neutrality -- Chapter 9. Living green: New lifestyle and social governance -- Chapter 10. Green city: Improving urban planning and governance -- Chapter 11. Digital economy to help achieve carbon neutrality -- Chapter 12. Investment amid carbon neutrality and sustainable development -- Chapter 13. Global carbon neutrality and China$1 (Bs commitment.s
Keywords: Economic development; Environmental policy; Sustainability; Valuation; Economic policy; Economic Growth; Environmental Policy; Sustainability; Investment Appraisal; Economic Policy